Neurodevelopment Outcome of Neonates Treated With Intraventricular Colistin for Ventriculitis Caused by Multiple Drug-Resistant Pathogens—A Case Series - Hussain, Kashif; Sohail Salat, Muhammad; Ambreen, Gul; Iqbal, Javaid (Frontiers in Pediatrics, 2021)
Background: Multiple-drug-resistant Gram-negative bacteria (MDR-GNB)-associated neonatal ventriculitis is a life-threatening complication that needs timely diagnosis and effective treatment with broad-spectrum antimicrobials in critical-care settings. Inadequate penetration of antibiotics through the blood–brain barrier also demands an intraventricular (IVT) route of administration. This study reports mortality and neurodevelopmental sequelae of neonates till 18 months of age, who received IVT-colistin for treating MDR-GNB associated ventriculitis. Methods: In a case series of seven neonates with ventriculitis due to MDR-GNB at NICU of Aga Khan University Hospital, Pakistan, between June 2015 and 2018, we reviewed IVT-colistin therapy in critically ill neonates. Treatment outcomes were assessed based on clinical sign's resolution and MDR-GNB eradication in subsequent CSF cultures. Neurodevelopmental outcomes were evaluated at 18 months after discharge. Results: The average birth weight was 1.38 kg (range: 1.02–1.5 kg), and the average gestational age was 30.7 weeks (ranged: 26–34 weeks). All neonates reported colistin-sensitive MDR-GNB in CSF, five with Acinetobacter baumannii, and polymicrobial CNS infection was found in two patients (one due to Klebsiella pneumonia and A. baumannii and one due to K. pneumonia and Escherichia coli). All neonates received IVT colistin and concomitant intravenous meropenem, and five of them also received intravenous colistin. One neonate died. At the 18-month assessment, only one neonate had cerebral palsy and hydrocephaly and 50% had seizure disorders. Conclusion: Practicing intraventricular antibiotics in the neonatal population is challenging but may be used successfully, especially to overcome the limitation of poor penetration through the blood–brain barrier.